2022
DOI: 10.3390/jof8101030
|View full text |Cite
|
Sign up to set email alerts
|

Gramiketides, Novel Polyketide Derivatives of Fusarium graminearum, Are Produced during the Infection of Wheat

Abstract: The plant pathogen Fusarium graminearum is a proficient producer of mycotoxins and other in part still unknown secondary metabolites, some of which might act as virulence factors on wheat. The PKS15 gene is expressed only in planta, so far hampering the identification of an associated metabolite. Here we combined the activation of silent gene clusters by chromatin manipulation (kmt6) with blocking the metabolic flow into the competing biosynthesis of the two major mycotoxins deoxynivalenol and zearalenone. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 48 publications
0
0
0
Order By: Relevance
“…MS 2 mass fragments of the FDDP-D [M + H]+ (RT5.70_m/z 503.3004) observed in our study do not match those reported by Seidl et al [27] for gramiketide B ([M + H] + m/z 503.3003). Rather, the MS 2 [M + H] + mass fragments reported for gramiketide B [27] closely match the MS 2 [M + H] + mass fragments of the C16 BGC unknown mass feature observed in our study as RT5.51_m/z 503.3004 from in planta wheat head challenge (Table S7). A potential mass feature corresponding to Seidl et al's proposed gramiketide A (m/z 521.3109) was also detected in our wild-type in planta extracts (m/z ∆ppm < ±5), albeit at detection intensities at the limit of detection of our instrument when searching using extraction ion chromatograms-the detected amounts were insufficient to carry out MS 2 comparison for further validation.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…MS 2 mass fragments of the FDDP-D [M + H]+ (RT5.70_m/z 503.3004) observed in our study do not match those reported by Seidl et al [27] for gramiketide B ([M + H] + m/z 503.3003). Rather, the MS 2 [M + H] + mass fragments reported for gramiketide B [27] closely match the MS 2 [M + H] + mass fragments of the C16 BGC unknown mass feature observed in our study as RT5.51_m/z 503.3004 from in planta wheat head challenge (Table S7). A potential mass feature corresponding to Seidl et al's proposed gramiketide A (m/z 521.3109) was also detected in our wild-type in planta extracts (m/z ∆ppm < ±5), albeit at detection intensities at the limit of detection of our instrument when searching using extraction ion chromatograms-the detected amounts were insufficient to carry out MS 2 comparison for further validation.…”
Section: Discussioncontrasting
confidence: 99%
“…For example, microarray expression profiles of F. graminearum C16 BGC genes significantly increase after 72 h postinoculation on barley and 96 h postinoculation on wheat followed by a subsequent decrease [8]. This result was recently corroborated using LC-HRMS profiling of F. graminearum-infected wheat heads, where postulated C16 BGC products along with DON were observed 72 h postinoculation, with concentrations increasing over time [27]. Transcriptomics experiments have also linked the co-expression of the C16 BGC with that of the fusaoctaxin BGC (C64) in F. graminearum, where transcripts of both BGC genes were observed to peak 64-96 h after infection in infected barley and wheat kernels followed by a subsequent decrease [7].…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations